Akulturasi dalam Turisme di Hindia Belanda - Sunjayadi, R Achmad (Paradigma: Jurnal Kajian Budaya, 2018)
As a form of cultural process, acculturation serves as an important factor in tourism. Usually, the hosts borrow the results of acculturation generated from tourism activities more than the tourists or guests do. Acculturation in tourism occurs not only in tourism practices today, but also in those in the past, including the tourism practices in Indonesia during the Dutch colonial era. This article discusses acculturation which became part of tourism activities in the Dutch East Indies by applying historical methods and Nunez’s concept of acculturation in tourism. By using guidebooks, newspapers, magazines, postcards, photographs, and travelogues as data sources, this article traced the result of acculturation at that time. Results show that acculturation really took place in the tourism activities in the Dutch East Indies. There were material objects and customs which served as tourism facilities and could be seen, performed, and enjoyed by the tourists. It can be concluded that at that time the tourists or guests borrowed the results of acculturation more than the hosts did.